Strategi Pembelajaran Bahasa Arab dalam Kemahiran Menulis (Al-Imla) Di Pondok Pesantren Al Khairaat Salilama Kecamatan Mananggu Kabupatenn Boalemo Provinsi Gorontalo - Muhammad Shadiq Ladiku; Titin Fatimah (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to determine the strategies used and what difficulties students experience in learning Arabic in writing skills (Al-Imla) at the Al-Khairaat Salilama Islamic Boarding School, Mananggu District, Boalemo Regency, Gorontalo Province. The approach used in this study is a qualitative approach, with data collection techniques through interviews, observation, and documentation. The results showed that the strategy for learning Arabic in writing skills (Al-Imla) was applied at the Al-Khairaat Salilama Islamic Boarding School, Mananggu District, Boalemo Regency, Gorontalo Province, had two strategies for implementing Arabic learning, namely the strategy learning in inside and outside the classroom.